Application of ionic liquids in food and environment. Issue 1 (September 2021) - Jia, Xiaoqiao; Liu, Baoyou; Zheng, Keyang
Abstract: Ionic liquids are substances composed entirely of cations and anions that have a low melting point and are usually liquid at or below room temperature. This paper introduces the application of ionic liquids in the field of food and environment field, the ionic liquids in food in the field of synthesis, food separation and purification, food pigment extraction as well as the environment in the field of wastewater treatment, air treatment, soil remediation and waste resource utilization research progress were reviewed, and the prospect of development is forecasted.